Progress as barbarism. Epistemic violence and philosophicide of the West against indigenous Cosmo-Spiritualities - ESTERMANN, Josef (Utopía y Praxis Latinoamericana, 2022)
In this paper, the author subjects the narrative of "interculturality" to a critique from an intercultural perspective, invoking the critical potential of intercultural philosophy in contrast to a culturalist "interculturality" light. The background of this analysis is the epistemic violence exercised by the West in the fields of knowledge, science, and education. This violence is particularly noticeable in the case of philosophy, leading to a sort of "philosophical homicide" (philosophicide) with respect to indigenous philosophies such as the Andean one in the case of Abya Yala. The paper concludes with some guidelines for the challenges that a critical intercultural philosophy must face in the XXI century.